KEDUDUKAN HAK ORANG ASING TERHADAP STATUS KEPEMILIKAN RUMAH - Hetty Hassanah; Wahyudi Wahyudi (Universitas Suryakancana, 2022)
One of the government's policies to accelerate development is to pave the way for investment from within the country and from abroad. Investors from abroad expect to own a house with a clear ownership status with the aim of ensuring the security of their investment, while the legal instruments governing home ownership by foreigners still lead to multiple interpretations. The research is descriptive analytical, using normative juridical methods and the resulting data is analyzed in a qualitative juridical manner. The results obtained from this study indicate that the land provisions are regulated in Government Regulation Number 103 of 2015 but in this regulation there are still controversies in its application. The government as a policy maker has an obligation to clearly regulate home ownership by foreigners as an effort to ensure legal certainty for foreign investors in investing in the country. The regulation must also protect the community by upholding a balanced justice between the community, businessmen and authorities